PENGARUH MODEL PEMBELAJARAN REALISTICS MATHEMATIC EDUCATION TERHADAP MOTIVASI DAN HASIL BELAJAR MATEMATIKA KELAS IV SD - Eka Putra, Randi; Sundahry, Sundahry; Meiliza, Selvira; Syaprida, Syaprida (Jurnal Muara Pendidikan, 2024)
The problem in the study focuses on the low motivation and learning outcomes of students in mathematics, although mathematics is an important subject, many students have difficulty understanding basic concepts.This experimental questionnaire research aims to determine the effect of the realistic mathematics Education learning model on the Motivation and Mathematics Learning Outcomes of Class IV SDN 102/II Sungai Kerjan. This type of research is Quan experiment. Population study This is student class IV SDN 102/II Sungai Kerjan. Amount sample study This is 44 students. Sample taken with use technique purposive sampling. Two classes were taken as samples in this study: the experimental and control classes. Class IV A has 22 students as class control using learning models, while IV B totalled 22 students as class experiments using learning models, such as realistic math education. Instruments used are questionnaires And sheet test results. Study students. Data was analyzed using a T-test. Results test hypothesis show motivation Study student t count 2.053 > t table 2018 shows motivation class experiment taller from on class control. Meanwhile, the results of Study student t count 2.578 > t table 2018 show that the results of the Study class experiment were taller than the class control. So that can conclude motivation And results Study with use learning models Realistic Mathematics Education influential to motivation And results Study mathematics class IV SDN 102/II Sungai Kerjan.